Treatment of sleep apnoea with tonsillectomy: a retrospective analysis using long-term follow-up data - Sjöblom Henrik M; Nahkuri Max; Suomela Miika; Jero Jussi; Piitulainen Jaakko M (SPRINGER, 2022)
Purpose: This single-group, retrospective, pre-test-post-test study was performed to examine clinical outcomes in treating obstructive sleep apnoea (OSA) with tonsillectomy alone and had the longest follow-up periods to date.
Methods: We analysed 151 tonsillectomies in our district between the years 2004 and 2018 that had either sleep apnoea or snoring listed as a diagnosis. Twenty-one patients met our criteria and were included. Patient records were analysed for home sleep apnoea test and Epworth Sleepiness Scale (ESS) scores.
Results: We defined success as a > 50% reduction of the Apnoea-Hypopnea Index (AHI) and a total AHI of < 20 post-surgery. The averages before surgery were an AHI of 22.3 and an ESS of 7.22. The success rate was 47.6% after tonsillectomy as the sole treatment for obstructive sleep apnoea in our adult population. Eleven patients were non-responders. The average ESS score reduction was 0.69 and did not reach statistical significance. With follow-up times ranging from 1.8 to 171 months, this study had the longest follow-up period compared to other existing studies. No patient with a follow-up longer than one year was a responder.
Conclusion: Our results support that tonsillectomy is an effective treatment for obstructive sleep apnoea in adults with tonsillar hypertrophy. With less severe OSA than those reported on previously, our patients also had less severe daytime sleepiness before surgery, and daytime sleepiness score reductions did not reach statistical significance. In the future, long-term results should be further analysed.